SUSTAINABLE CONTROL OF LEAF HOPPER (Amrasca biguttula biguttula Ishida) ON GRAPE VINE (Vitis vinifera L.) - GHOSH, SUNIL KUMAR; KARMAKAR, RAJIB (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Leaf hopper (Amrasca biguttula biguttula Ishida.) causes heavy damage to grape vine (Vitis vinifera L.). The pest causes a limiting factor in the commercial production of grapes and many other crops in West Bengal. It was observed that spinetoram 10% w/w + sulfoxaflor 30% w/w WG @ 100, 120 and 140 a.i. g /ha, one dose of spinetoram 12% SC w/v (11.7%w/w), sulfoxaflor 24% w/v (21.8% w/w) SC, emamectin benzoate 5% SG and buprofezin 25% SC @ 30, 90, 11 and 250 a.i. g /ha, respectively were sprayed to compare their efficacy against leaf hopper. The spinetoram 10% w/w + sulfoxaflor 30% w/w WG @ 140 g a.i./ha provided to be the best control of leaf hopper and spinetoram 10% w/w + sulfoxaflor 30% w/w WG @ 120 g a.i./ha. Same trends have also been reflected in yield of grapes. The tested insecticides were also found very safe to predators i.e. Menochilus sp., Syrphus sp. and Chrysoperla sp. of grapes insect-pests.